2010
DOI: 10.1093/hmg/ddq158
|View full text |Cite
|
Sign up to set email alerts
|

An accumulation of non-farnesylated prelamin A causes cardiomyopathy but not progeria

Abstract: Lamin A is formed from prelamin A by four post-translational processing steps-farnesylation, release of the last three amino acids of the protein, methylation of the farnesylcysteine and the endoproteolytic release of the C-terminal 15 amino acids (including the farnesylcysteine methyl ester). When the final processing step does not occur, a farnesylated and methylated prelamin A accumulates in cells, causing a severe progeroid disease, restrictive dermopathy (RD). Whether RD is caused by the retention of farn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
129
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(138 citation statements)
references
References 48 publications
8
129
0
1
Order By: Relevance
“…[38][39][40][41] However, recent studies with a CAAX motif mutant or mice lacking farnesyltransferase expression in keratinocytes suggested that, at least for LA, incorporation into the lamina does not require farnesylation. 42,43 The only two studies …”
Section: Resultsmentioning
confidence: 99%
“…[38][39][40][41] However, recent studies with a CAAX motif mutant or mice lacking farnesyltransferase expression in keratinocytes suggested that, at least for LA, incorporation into the lamina does not require farnesylation. 42,43 The only two studies …”
Section: Resultsmentioning
confidence: 99%
“…The "mature lamin A" mice were healthy and fertile, and the lamin A in their tissues was positioned normally along the rim of the cell nucleus, indistinguishable from lamin A in the tissues of wild-type mice. Davies et al (37) found that mice expressing nonfarnesylated prelamin A developed cardiomyopathy late in life, but the nonfarnesylated prelamin A was positioned normally at the nuclear rim. Neither the distinctive phenotypes of mature lamin A and nonfarnesylated prelamin A mice nor the nuclear rim localization of the lamin A proteins in these mice could have been predicted from cell culture studies alone.…”
Section: Discussionmentioning
confidence: 99%
“…Lmna nPLAO/nPLAO mice, expressing only non-farnesylated prelamin A, appeared normal for the first 20 weeks of life, but developed a cardiomyopathy and died earlier than healthy mice (median survival in female mice 49.5 weeks, in male mice 38.5 weeks). 23 By contrast, the presence of farnesylated progerin next to mature lamin A in classical HGPS disturbs the nuclear integrity and results in the typical progeroid phenotype with death in early adolescence.…”
Section: Discussionmentioning
confidence: 99%